Cooperative output regulation problem of multi-agent systems with stochastic packet dropout and time-varying communication delay. Issue 17 (November 2018) - Liu, Zili; Yan, Weisheng; Li, Huiping; Small, Michael
Abstract: In this paper, we deal with the cooperative output regulation problem of linear multi-agent systems on a directed network topology subject to both stochastic packet dropout and time-varying communication delay. On the basis of introducing a queuing mechanism, a distributed state feedback control algorithm is proposed. Then the continuous-time multi-agent systems with piece-wise constant control are converted into discrete-time systems. Under some standard assumptions, the necessary and sufficient conditions under which the tracking errors of followers approach to the origin asymptotically are proposed for different exosystems. Finally, the proposed results are verified via two examples.